MENINGKATKAN KEAKTIFAN SISWA MELALUI DEBAT DAN PENGUNAAN MEDIA BERGAMBAR PADA PELAJARAN BAHASA INDONESIA SISWA DI KELAS X IPA SMA N UNGGUL DHARMASRAYA - Gusni, Nenri; Syofiani, Syofiani (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
Students' active speaking is a learning target that must be mastered. This research aims at increasing students activity through debate and pictorial media in Bahasa Indonesia lessons. Type of this research is classroom action research. The subjects were class X IPA at SMAN Unggul Dharmasraya, consisting of 21 students. There were 9 boys and 12 girls. There are 7 indicators of students activity through pictorial media; 1) understanding the picture, 2) conveying arguments about the pictures, 3) responding and think quickly, 4) making a motion, 5) supporting and rejecting the motion, 6) presenting data and evidence, and 7) making a closing sentence. The results of the pre-observation research shows that there are 9 (43%) students active in the learning process. Furthermore, in the first cycle of first meeting, there are two active groups (29%) speaking and enthusiastic in discussing. In the first cycle of second meeting, there are 3 groups (43%) are active. Then in the second cycle of first meeting, there are four groups (57.1%) active. In the second cycle of secong meting, there are 6 groups (85.7%) are actives. It can be said that debate and pictorial media can increase students activity in learning.